Investments - Zvi Bodie (McGraw-Hill Education, 2024)
This edition introduces students to current investment issues that are the concerns of all investors. Our book arms students with the skills to conduct a sophisticated assessment of current issues and debates covered by both the popular media and more specialized finance journals. Whether they plan to become an investment professional or simply a sophisticated individual investor, they will find these skills essential. In an effort to link theory to practice, many features of this text are designed to be consistent with and relevant to the CFA curriculum, including end-of-chapter problems from past CFA exams